Robust polarization gradient cooling of trapped ions - Li, Wenbing; Wolf, Sebastian; Klein, Lukas; Budker, Dmitry; Duellmann, Christoph E.; Schmidt-Kaler, Ferdinand (New Journal of Physics, 2022)
We implement three-dimensional polarization gradient cooling (PGC) of trapped ions. Counter-propagating laser beams near 393 nm impinge in lin ⊥ lin configuration, at a frequency below the S1/2 to P3/2 resonance in 40Ca+. Our measurements demonstrate that cooling with laser beams detuned to lower frequencies from the resonance is robust against an elevated phonon occupation number and works continuously in the crossover from regular Doppler cooling to detunings of tens of linewidths. It is thus robust against heating events and also works well for an initial ion motion far out of the Lamb-Dicke regime. We show that PGC performance strongly depends on residual micromotion (MM) and find PGC working for a MM modulation index β < 0.1. Still, we find that the spectral impurity of the laser field affects both, cooling rates and cooling limits. Thus, a Fabry-Pérot cavity filter is employed to efficiently suppress amplified spontaneous emission of the diode laser. We demonstrate mean phonon numbers for a single ion of 5.4(4) at a trap frequency of 2π × 285 kHz and 3.3(4) at 2π × 480 kHz, in the axial and radial directions, respectively.
Created from Fastlane, Scopus look-up
Keywords: laser cooling; polarization gradient cooling; sub-Doppler cooing; trapped ions